Evaluating Prediction Score For Success of Trial of Labor After Cesarean (TOLAC) - Baqai, Shehla; Afroze, Sadaf (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the success rate for trial of labor after cesarean section in women with good prediction score. Study Design: Cross sectional (analytical) study. Place and Duration of Study: Department of Obstetrics and Gynecology, PEMH Rawalpindi, from Dec 2017 to Jun 2018. Methodology: A total of 141 women with previous delivery by caesarean section, planned for trial of labor with good prediction score of ≥8 were included in the study. All patients were then allowed to labor spontaneously. Data was collected for success rate after trial of labor Results: Age range in this study was from 18-35 years with mean age of 29.234 ± 2.13 years, mean gestational age 38.531 ± 0.99 weeks, mean weight 63.290 ± 9.97 Kg, mean height 1.532 ± 0.08 meter and mean BMI was 27.097 ± 4.59 Kg/m2. Success rate was seen in 86.5% patients. Conclusion: In conclusion, a prediction model was proposed that can provide useful insights to envisage VBAC success rate for the pregnant women having history of caesarean delivery at the time of admission.